(untitled) (Revista Logos Ciencia & Tecnología, 2024)
The methodological details of a numerical computer simulation modelling the fall of a person who suffers several collisions during their descent are presented. In one of these collisions, their arm makes contact with a portion of the structural framework of the building from which they are falling. The body ultimately reaches a point of rest within a corridor, rather than at the lowest point of the building. Such circumstances render the case distinctive. Such tools are useful for evaluating hypotheses in forensic investigations, and thus require the adherence to a clearly defined set of steps in the construction of scenarios and the establishment of initial conditions. Subsequently, the simulation must be evaluated until the input data that allows for the most coherent recreation with the evidence, particularly in regard to serious injuries such as fractures, is reached. Furthermore, it is crucial to assess the resilience of the simulation to minor alterations in the initial parameters. Additionally, the values of displacement, velocity, and acceleration during the incident must be examined, as these data can be linked to specific instances in the formation of evidence. Finally, to evaluate the software, a basic simulation test is presented to demonstrate the alignment between the numerical outcomes and the theoretical physics of falling bodies.